2022
DOI: 10.1002/ffj.3710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipid on formation of Maillard and lipid‐Maillard meaty flavour compounds in heated cysteine‐xylose‐methyl linoleate system

Abstract: The effect of lipid level and reaction temperature and time on the heated cysteinexylose reaction to form meaty flavours was investigated. The presence of 1% or 2% methyl linoleate inhibited the formation of volatile sulfur-containing compounds and heterocyclic compounds via the Maillard reaction, that is Maillard compounds. However, the former was better because of the moderate inhibition and more compounds generated from the lipid-Maillard interaction, that is lipid-Maillard compounds. Partial least squares-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The content of thiophene compounds in SMHM2 was 0.197 μg/g. Previous studies had showed that 3-methylthiophene-2-formaldehyde and 3-methylthiophene in thiophene were the reasons for sulfur flavor in cooked meat products ( Wang, Xie, Zhang, Xu, & Yang, 2022 ). Pyrazines were the main nitrogenous compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The content of thiophene compounds in SMHM2 was 0.197 μg/g. Previous studies had showed that 3-methylthiophene-2-formaldehyde and 3-methylthiophene in thiophene were the reasons for sulfur flavor in cooked meat products ( Wang, Xie, Zhang, Xu, & Yang, 2022 ). Pyrazines were the main nitrogenous compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The Maillard reaction, a nonenzymatic reaction between carbonyl compounds formed by the oxidation of reducing sugars, aldehydes, ketones and fats in the raw meat and proteins, peptides, amino acids, amines and ammonia, often occurs in fermented meat products [17]. Amino and carbonyl groups undergo dehydration condensation to form glucosamine, which then reacts with aldehydes, hydrogen sulfide and amino acids after rearrangement and deoxygenation to form various aroma substances [12].…”
Section: Formation Of Flavour Substances In Fermented Meat Productsmentioning
confidence: 99%
“…Maillard reaction between sugar and protein has been widely studied (Melton, 1999; Bassam et al ., 2022; Sun et al ., 2022). It is the primary way to produce flavour during high‐temperature cooking methods such as barbecue and frying (Wang et al ., 2022). Although it is generally believed that Maillard reaction can be carried out at low temperatures (<100 °C) (Zhou et al ., 2021), it cannot be the main source for flavour of foods (Jousse et al ., 2002; Wei et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%